Pendampingan Inventarisasi Data Grafis Bangunan Rumah Kampung Adat Kranggan - Ali, Abdullah; Juwono, Sudarmawan; Solo, Adrianus; Riansyah, Teguh Iman (LPPM Universitas Bung Karno, 2023)
Kampong Kranggan is a traditional village in Bekasi City that still survives with the building of stilt houses and the Babaritan ceremony as a cultural ritual. Architectural resilience amidst the modernization of urban areas makes this traditional village unique and has a distinctive character. The community service carried out aims to carry out an architectural inventory of the graphic data on the building of the Kranggan traditional village house architecturally. With a sustainable mentoring model, the inventory of traditional houses is a preservation database. Community service uses a participatory method approach, which applies observation and interviews as instruments for processing and presenting data. Stages of architectural surveys, measurements, sketches, and photo documentation, by involving the owners of traditional house buildings in a participatory manner. From the results of the data collection, a focus group discussion was carried out to dig up in-depth information, and an inventory of data was carried out by digitally depicting the shape of buildings and areas. The result of this community service is the availability of graphical data for the people of the Kranggan Traditional Village and the Jatirangga Village government. The process of community service is expected to be able to encourage increased awareness, initiatives, innovation, and community participation in the preservation of cultural heritage and increase the usability of house buildings as community assets in the development of the creative economy become the basis for the Kampong Kranggan Traditional Village preservation movement and of course, can be used in regional planning in the City Bekasi.